Propuesta de un sistema de tratamiento de agua residual industrial en el proceso de elaboración de la panela en la empresa Doña Panela Ltda (2019)
To develop this proposal, we will develop a physicochemical analysis of the water from the panela production process, through which the state of the effluent was characterized. Following this, three treatment alternatives were proposed: coagulation / flocculation, electrocoagulation and activated sludge. Which are evaluated by means of a matrix of criteria selection and the two best alternatives are chosen: coagulation / flocculation and electrocoagulation, respectively. Through experimental development on a laboratory scale of the coagulation / flocculation process, selecting aluminum polychloride (PAC) as the best coagulant for this process, a concentration of 10% and a dosage of 200 ppm; showing reduction in turbidity and COD by 19.75% (67.45 NTU) and 11.25% (2210 mg / L) respectively. Regarding the electrocoagulation process, evaluate on a laboratory scale, determine which most efficient combination of factors is: Retention time 30 minutes and, with a constant current intensity of 15 Volts, obtain a removal of the contaminating charges, where the COD presented a reduction of 40.97% recording the value of 1619 mg / L and turbidity was reduced 81.94% registering a figure of 15.49 NTU. For this project, the best process for removing contaminants for wastewater from the panela production process is defined as electrocoagulation. It is important to highlight the electrocoagulation system presented with reductions of contaminants affected in terms of the initial parameters evaluated. However, when comparing the results obtained with the current legal regulations (Resolution 0631 of 2015), the required compliance cannot be given to them.